2012
DOI: 10.1021/jm201286z
|View full text |Cite
|
Sign up to set email alerts
|

7,8-Dichloro-1-oxo-β-carbolines as a Versatile Scaffold for the Development of Potent and Selective Kinase Inhibitors with Unusual Binding Modes

Abstract: Development of both potent and selective kinase inhibitors is a challenging task in modern drug discovery. The innate promiscuity of kinase inhibitors largely results from ATP-mimetic binding to the kinase hinge region. We present a novel class of substituted 7,8-dichloro-1-oxo-β-carbolines based on the distinct structural features of the alkaloid bauerine C whose kinase inhibitory activity does not rely on canonical ATP-mimetic hinge interactions. Intriguingly, cocrystal structures revealed an unexpected inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 51 publications
3
64
0
Order By: Relevance
“…[34] Against expectation, the compound proved to be completely inactive at the concentrations tested. Given that kinase inhibitors anchored to the hinge region through one or two halogen bonds have been described, [35] we probed if introducing a bromine atom to the 3- . QM relaxed torsional scan (3608 in 108 steps) of the tofacitinib side chain relative to the planar heterocyclic core.…”
Section: Resultsmentioning
confidence: 99%
“…[34] Against expectation, the compound proved to be completely inactive at the concentrations tested. Given that kinase inhibitors anchored to the hinge region through one or two halogen bonds have been described, [35] we probed if introducing a bromine atom to the 3- . QM relaxed torsional scan (3608 in 108 steps) of the tofacitinib side chain relative to the planar heterocyclic core.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of multiple halogen bonds stabilizing protein− ligand complexes has also been reported by Knapp, Bracker, and co-workers in the complex of a 6,7-dichloro-substituted indole ligand with the carbonyl oxygens of the hinge region of the CDC-like kinase 3 (CLK3), 313 and in the complex of dichloro-substituted carbolines with PIM1 kinase (PIM = proviral integration site in moloney murine leukemia virus). 314 Baumil and co-workers have demonstrated that multiple Cl··· O halogen bonds are responsible for the selectivity of DRB (5,6-dichlorobenzimidazone-1-β-D-ribofuranoside) toward cyclin-dependent kinase 9 (Cdk9) (Cdk9 inhibition contributes to the anticancer effect of many Cdk inhibitors, and as a consequence its selective inhibition is of great interest). 315 DRB binding induces a conformational change in Cdk9, and binds via two Cl···O XBs (Figure 77), with the binding supplemented by an orthogonal NH···X HB to the chlorine atom's negative belt of electron density (PDB entry 3MY1).…”
Section: Analysis Of the Protein Data Bank: Halogen Bonds To Amino Acidsmentioning
confidence: 99%
“…Superpositions of the 58 Pim-1-inhibitor complexes submitted to the PDB using secondary-structure matching in Coot (Emsley & Cowtan, 2004) revealed that only three other inhibitors, -carboline ligand I (PDB entry 3cxw; Huber et al, 2012), -carboline ligand II (PDB entry 3cy2; Huber et al, 2012) and one of the 3H-benzo[4,5]-thieno[3,2-d]pyrimidin-4-one inhibitors (PDB entry 3jxw; Tao et al, 2009), also raise the P-loop. However, the conformation in compound 1 has the closest proximity to the 3 strand.…”
Section: P-loop Conformationmentioning
confidence: 99%